ANALISA KADAR TIMBAL DALAM DARAH TUKANG BECAK DI WILAYAH SURABAYA UTARA - Faradilah, Yasmine; Christyaningsih, Juliana; Lestari, Indah (Analis Kesehatan Sains (e-Journal), 2024)
Lead (Pb) is one of the heavy metals with high toxicity which can pollute an environment and affect survival. Lead that enters the body is excreted into the bones, teeth and hair. A small amount of Pb, stored in the brain. 99% of lead binds to erythrocytes. The purpose of this study was to analyze the levels of lead (Pb) in the blood of pedicab drivers at Jembatan Merah, North Surabaya. This type of research is a type of descriptive research conducted at the Toxicology Laboratory, Campus of Technology, Medical Laboratory of the Surabaya Polytechnic, Surabaya Center for Standardization and Industrial Services from October 2022 to May 2023. The research sample was 20 venous blood of pedicab drivers at the Red Bridge in North Surabaya with the following criteria: has an age of more than 30 years and has a service life of more than 2 years and then tested using the Atomic Absorption Spectrophotometry (AAS) method. The results of the 20 samples showed that blood lead levels in pedicab drivers in the North Surabaya Region were still within the normal threshold set by WHO in 2021, namely <5 µg/dl or 0.05 mg/L.